A bibliometric analysis of wifi accessibility on university: for future research direction - Che Yusoff Gemeti, Mazlam; Ahmad Zukarnain, Zuriani; Abdul Rahman @ Abdul Rashid, Noorihan; Sapiai, Nur Shaliza; Haron, Haryani (Faculty of Information Management, 2025)
This paper investigates the availability of free WiFi on college campuses and how availability interacts with students to compose their social and academic engagement. Utilising a bibliometric method First, this study provides an overview of significant authors, themes, and research trends regarding WiFi accessibility in higher education institutions. The research data were obtained using the Scopus database and analyzed by VOSviewer, Microsoft Excel, and SPSS 25.0. The results of the study show that WiFi can promote higher academic accomplishment, collaborative learning, and participation in extracurricular activities. However, issues such as a lack of reliable WiFi and thin coverage need to be resolved to ensure students get the best educational experience they can. It says universities should update new technology and maintenance, so students and faculty have a stable and fast internet connection to the entirety of campus.